Cloud-Based Game Server Infrastructure AT PT. Games Karya Nusantara (Majamojo) - Ahmad Yusuf Al Majid; Suryadiputra Liawatimena (Publikasi Indonesia, 2023)
In the era of the game publishing industry, MAJAMOJO collaborates with game developers in developing game server infrastructure in Indonesia, by realizing the adoption of cloud computing using the Roadmap for Cloud Computing Adaption (ROCCA) method. Cloud computing implementation by following 5 stages of modification of the ROCCA adoption model, namely the analysis, design, adoption, migration, and management stages. By using Amazon Web Service (AWS) Cloud Service (CSP) services. Cloud computing adoption is carried out by developing game server infrastructure as connectivity between the client and the game server. The analysis is carried out by collecting data and interviews from speakers, in the design of the cloud computing technology to be used, the selection of the technology is based on the results of the analysis stage, then the adoption process prepares the cloud infrastructure to be built, based on software selection and setting up servers with recommended specifications, then migration is the core of the cloud computing adoption process, Where the process transfers the system from the physical server to the virtual server, new management will be executed if the adoption and migration process has been completed with the Game Server and Game Client connectivity indicators running normally. With the application of cloud computing based on the characteristics of the cloud itself, it is flexible, scalable, and safe to access over the internet.